1998
DOI: 10.1002/(sici)1097-4644(19980915)70:4<442::aid-jcb2>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic cleavage and activation of PAK2 during UV irradiation-induced apoptosis in A431 cells

Abstract: Exposure of mammalian cells to ultraviolet (UV) light elicits a cellular response and can also lead to apoptotic cell death. In this report, we show that a 36-kDa myelin basic protein (MBP) kinase detected by an in-gel kinase assay can be dramatically activated during the early stages of UV irradiation-triggered apoptosis of A431 cells. Immunoblot analysis revealed that this 36-kDa MBP kinase could be recognized by an antibody against the C-terminal regions of a family of p21Cdc42/Rac-activated kinases (PAKs).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…In agreement with the model a peptide from the PAK1 regulatory region (amino acids 83-149) can be used as a dominant-negative inhibitor of PAK activity both in itro and in i o [82], and mutants of the PAK inhibitory domain are found to have constitutive kinase activity [82,83]. Equally, cleavage of PAK-2 (and of PKN, see below) by caspases, which occurs during apoptosis, also removes its regulatory domain and creates a constitutively active protein [84,85]. Two kinases which are Rho effectors have also been reported to contain autoinhibitory domains, ROK and PKN.…”
Section: The Activation Of Effectors By Rho Gtpasesmentioning
confidence: 99%
“…In agreement with the model a peptide from the PAK1 regulatory region (amino acids 83-149) can be used as a dominant-negative inhibitor of PAK activity both in itro and in i o [82], and mutants of the PAK inhibitory domain are found to have constitutive kinase activity [82,83]. Equally, cleavage of PAK-2 (and of PKN, see below) by caspases, which occurs during apoptosis, also removes its regulatory domain and creates a constitutively active protein [84,85]. Two kinases which are Rho effectors have also been reported to contain autoinhibitory domains, ROK and PKN.…”
Section: The Activation Of Effectors By Rho Gtpasesmentioning
confidence: 99%
“…Also, in contrast to Pak1 and Pak3, Pak2 can be activated via cleavage by caspase proteases to release a constitutively active C-terminal fragment (Pak2p34). Caspaseactivated Pak2p34 has been observed after cells are exposed to death stimuli such as Fas ligand, TNFα, heat shock or UV radiation Rudel and Bokoch, 1997;Tang et al, 1998). Studies have suggested that the formation of Pak2p34 mediates cell death in response to these stimuli and that it is an essential mediator of cell death in response to Fas-related signals (Rudel and Bokoch, 1997;Rudel et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, PAK2 has been reported to be activated by cellular stresses such as hyperosmolarity and DNA damage (19,20). In Jurkat T cells, PAK2 is activated after cleavage by caspase 3 and appears to mediate some of the membrane and morphological changes characteristic of programmed cell death (21).…”
mentioning
confidence: 99%